Contribution of classical end-joining to PTEN inactivation in p53-mediated glioblastoma formation and drug-resistant survival - Youn-Jung Kang (Nature Portfolio, 2017)
We know that defects in DNA repair genes are associated with cancer development. Here the authors eliminate XRCC4, a non-homologous end-joining protein, and p53 in the developing brain and find that this causes glioblastoma development as a consequence of reduced PTEN function.